2012
DOI: 10.4172/plastic-surgery.1000725
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral reduction mammoplasty following breast cancer: A case-control study

Abstract: S ymptoms of breast hypertrophy can affect post-treatment breast cancer patients. The true incidence of breast hypertrophy in the breast cancer population is unknown, as is the number of such patients seeking reduction mammoplasty surgery following breast cancer treatment. These patients have usually undergone lumpectomies followed by postoperative radiation therapy and chemotherapy. Although there can be changes in the shape and size of the treated breast as a result of lumpectomy and radiation, it is usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
0
12
1
1
Order By: Relevance
“…Several risk factors associated with the occurrence of fat necrosis after surgery have been proposed, which include neoadjuvant chemotherapy, adjuvant radiotherapy, high BMI, and uncontrolled underlying disease [37][38][39][40]. However, there was no significant factor associated with fat necrosis in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…Several risk factors associated with the occurrence of fat necrosis after surgery have been proposed, which include neoadjuvant chemotherapy, adjuvant radiotherapy, high BMI, and uncontrolled underlying disease [37][38][39][40]. However, there was no significant factor associated with fat necrosis in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…The overall incidence of complications of 11 studies [6, 11, 14, 15, 17, 18, 2024] was 11.0% (ranged 5% to 56%), while the rest [5, 19, 2527] reported only some specific complications, lacking the total quantities. Various operative techniques were used, in which the most frequent technique was the inferior pedicle with an average percentage of 46.0%.…”
Section: Resultsmentioning
confidence: 99%
“…We finally selected 3 studies [2527] reporting radiation therapy and complications after RM. The test for heterogeneity was not significant (p for heterogeneity = 0.46; I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported acceptable complication rates in small series of patients with a history of breast irradiation and subsequent treatment with reduction mammaplasty. [13][14][15][16][17][18] However, these reports have used traditional approaches to breast reductions using the inferior pedicle technique and, although the results were acceptable overall, a few patients suffered from major complications necessitating the use of a latissimus flap for salvage. In the current report, we present our experience with a less invasive approach using the central mound technique to preserve skin and glandular blood supply and enabling us to perform reduction mammaplasty with improved symmetry.…”
mentioning
confidence: 95%